1997
DOI: 10.1111/j.1600-0447.1997.tb10146.x
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings in patients with affective disorder: a meta‐analysis

Abstract: A review of the literature on primarily magnetic resonance imaging (MRI) scans of patients with affective disorders is presented. Several studies have indicated an increased ventricle/brain ratio and other signs of cerebral atrophy, as well as an increased frequency of lesions (so-called signal hyperintensities) in the brains of unipolar and bipolar patients. This notion is strongly supported by two meta-analyses performed in the present study. The lesions are often localized in the frontal lobes and the basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
3
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(160 citation statements)
references
References 82 publications
3
144
3
9
Order By: Relevance
“…217 T2 hyperintensities in white and grey matter are probably the most replicated structural finding in BD. According to meta-analyses, the risk of WMH in bipolar patients is over three times higher than that found in psychiatrically healthy control subjects, 218,219 although several studies have reported negative results. [220][221][222] Genetic factors account for the largest proportion of variation in WMH volumes.…”
Section: Basal Gangliamentioning
confidence: 99%
“…217 T2 hyperintensities in white and grey matter are probably the most replicated structural finding in BD. According to meta-analyses, the risk of WMH in bipolar patients is over three times higher than that found in psychiatrically healthy control subjects, 218,219 although several studies have reported negative results. [220][221][222] Genetic factors account for the largest proportion of variation in WMH volumes.…”
Section: Basal Gangliamentioning
confidence: 99%
“…Indeed, several studies have reported decreased or increased volumes of the subgenual gyrus and the AH complex in patients with unipolar and bipolar affective disorders, 3,12 but the empirical evidence of WM abnormalities in these regions is less clear. Several studies have reported increased WM hyperintensities in general [13][14][15] and in frontal brain regions in particular. 16,17 Similarly, voxel-based morphometry studies have shown a significantly reduced WM density in prefrontal regions encompassing frontostriatal connections.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been reported that patients with bipolar disorder more frequently have subcortical hyperintensity (SCH) lesions in the brain detected by T 2 -weighted magnetic resonance imaging (MRI) than do agematched healthy volunteers. 4,5 Subcortical hyperintensity in patients with bipolar disorder is not related to cardiac risk factors 6,7 but to positive family history, which suggests it may not be attributable to merely ischemic lesions. 8 Although its histopathological basis has never been reported, our recent study using phosphorus-31 magnetic resonance spectroscopy suggested that SCH in subjects with bipolar disorder might have a different biochemical basis to that in healthy aged subjects.…”
Section: Introductionmentioning
confidence: 99%